An amorphous lanthanum–iridium solid solution with an open structure for efficient water splitting. Issue 25 (16th June 2020) - Sun, Wei; Ma, Chenglong; Tian, Xinlong; Liao, Jianjun; Yang, Ji; Ge, Chengjun; Huang, Weiwei
Abstract : The first time a lanthanum–iridium amorphous solid solution with a novel nano flute-like morphology was synthesized for high activity for water splitting. Abstract : The lanthanum–iridium amorphous metal oxides with a novel flute-like nanostructure (La–Ir NF) were synthesized from the perspective of controlling the material's nanoscale morphology and crystal structure. The iridium mass ratio of the prepared La–Ir NF was only 38.8% (wt%), and it shows outstanding OER activity with a lower onset potential and Tafel slope, as well as a 12-fold higher mass activity than that of crystalline IrO2 oxides. Physical and chemical structural characterization experiments reveal that the amorphous La–Ir NF with a shorter atomic distance and the presence of La ions result in a lower symmetry of the IrO6 octahedron. The flute-like open structure increases the utilization efficiency of Ir atoms and the 5d orbital electron reconfiguration in the distorted IrO6 coordination is responsible for the excellent OER activity of the La–Ir NF. Our present study suggests that the amorphous open-structure morphology strategy is a promising way to prepare more efficient electrocatalysts, which can probably be applied to other transition metal oxides.